Case Report: A Rare Cause of Stridor and Hoarseness in Infants—Congenital Laryngeal Web - Wang, Yanyan (Frontiers in Pediatrics, 2022)
Background: Congenital laryngeal web is a rare disease that can cause stridor, dyspnea, hoarseness and other symptoms. Children with this disease generally have stridor, weak crying and hoarseness at birth, but these symptoms can also occur during the days, weeks, months, even years after birth. Respiratory tract infection will obviously aggravate these manifestations, and recovery is slow after symptomatic treatment. Neck computerized tomography (CT) and laryngoscopy can detect and diagnose this disease. It is important that the disease can be considered and examined in infants with recurrent stridor and persistent hoarseness after birth. Case Summary: We report a 23-month-old boy who was admitted to hospital due to stridor and hoarseness after birth. Combined with the results of laryngoscopy, he was diagnosed with congenital laryngeal web, and was treated with carbon dioxide (CO2) laser and cryotherapy by bronchoscope. The prognosis was good. Conclusion: Congenital laryngeal web is a rare but challenging laryngeal lesion. It is very important that the disease can be considered and examined for infants with recurrent stridor and persistent hoarseness after birth. The treatment strategy after diagnosis should be determined according to the classification of laryngeal web and the severity of children's symptoms.